El lago de los cisnes : suite de ballet - La Orquesta de Filadelfia; Ormandy, Eugen (San José, Costa Rica : INDICA)
Sumario: Música de ballet
Keywords: BALLET; TCHAIKOVSKY, PETER ILICH, -- 1840-1893; GRABACIONES SONORAS